2020
DOI: 10.1016/j.arr.2020.101166
|View full text |Cite|
|
Sign up to set email alerts
|

Benefits and harms of exercise therapy in people with multimorbidity: A systematic review and meta-analysis of randomised controlled trials

Abstract: Objectives To investigate the benefits and harms of exercise therapy on physical and psychosocial health in people with multimorbidity. Design Systematic review of randomised controlled trials (RCTs). Data sources MEDLINE, EMBASE, CENTRAL and CINAHL from 1990 to April 20th, 2020 and Cochrane reviews on the effect of exercise therapy for each of the aforementioned conditions, reference lists of the included studies, the WHO registry and citation tracking on included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 64 publications
5
93
0
6
Order By: Relevance
“…This study has several unavoidable limitations including the relatively small sample size, the short follow up duration, and the limited human physiological parameters that were measured. Although the effectiveness of the aerobic exercise training can be evaluated after 12 weeks in most studies [ 15 ], we designed an intervention wherein we combined the training program with motivational interviewing; hence, follow-up on adherence to physical activity recommendations and behavioral change-related outcomes in a longer period (24–48 weeks) with more repeat measures is recommended [ 26 ]. Moreover, although we had evaluated the gold standard outcomes of the cardiorespiratory fitness, other parameters such as physical functioning and quality of life are also important to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has several unavoidable limitations including the relatively small sample size, the short follow up duration, and the limited human physiological parameters that were measured. Although the effectiveness of the aerobic exercise training can be evaluated after 12 weeks in most studies [ 15 ], we designed an intervention wherein we combined the training program with motivational interviewing; hence, follow-up on adherence to physical activity recommendations and behavioral change-related outcomes in a longer period (24–48 weeks) with more repeat measures is recommended [ 26 ]. Moreover, although we had evaluated the gold standard outcomes of the cardiorespiratory fitness, other parameters such as physical functioning and quality of life are also important to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence showed that the benefits of individualized aerobic exercise training or therapy could be beneficial for not only healthy middle-aged and older adults [ 11 ], patients with hemodialysis [ 12 ], cancer [ 13 ], but also of those with other chronic diseases [ 14 ]. Based on a systematic review, for patients with multimorbidity, exercise interventions could improve physical function, reduce depression and anxiety symptoms, and improve health-related quality of life [ 15 ]. However, these studies rarely discussed the outcomes of physical activity (PA) and health-related physical fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical therapy interventions should focus on increasing physical activity and structured, supervised exercise programs as these have been shown to benefit both hip/knee OA and anxiety or depressive symptoms. 19,20,51,52 Evidence suggests that many types of exercise are beneficial for both hip/knee OA and anxiety or depression, so choice should be guided by patient preference and goals. 19,20,51,53 Patients with anxiety or depressive symptoms may particularly lack motivation to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,51,52 Evidence suggests that many types of exercise are beneficial for both hip/knee OA and anxiety or depression, so choice should be guided by patient preference and goals. 19,20,51,53 Patients with anxiety or depressive symptoms may particularly lack motivation to exercise. 54 Incorporating principles of behaviour change including social support, self-efficacy, active choices, goal setting and positive reinforcement may be beneficial for maximizing patient participation and adherence to exercise long-term.…”
Section: Discussionmentioning
confidence: 99%